Noncommutative Orlicz–Hardy spaces associated with growth functions - Abdurexit, Abdugheni; Bekjan, Turdebek N. (Journal of mathematical analysis and applications, 2014)
In this paper, we first present several basic properties of growth functions, and then prove a Hölder type inequality on noncommutative Orlicz spaces associated with a growth function. Moreover, we prove Riesz and Szegö type factorization theorems and the contractivity of the conditional expectation on noncommutative Orlicz–Hardy spaces associated with a growth function.